Optimalisasi Presensi dengan Implementasi QR-Code dan Real-Time Notifikasi Berbasis Flutter Mobile di SMK Al-Manshyuriyah Tasikmalaya - Adi Dadan Ramdana; Syafari Suryo Pranoto; Mia Sumiarsih; Mohammad Indra Andriana; Nurjaman (TEMATIK, 2023)
Student attendance in class is very important and closely related to proof of attendance in teaching and learning activities. The progress of the world of education always follows the development of Information Technology, various technological systems are used to help achieve the teaching and learning process. Currently, at SMK Al-Manshyuriyah the attendance process still uses the manual method of students affixing signatures or teachers calling each student, this condition risks invalid, lost attendance data and affects the integrity of the data. The current condition is that parents know that their children go to school, but the reality is that students do not attend class and do not fill in the attendance. So a system is needed that can record attendance data that is maintained in data quality and real-time information media to find out student attendance in attending lessons that can be known by schools and parents. The purpose of this research is to create a presence model with a QR-Code that changes every lesson according to the subject, day and hour as well as an attendance report that can be known in real-time. Research with qualitative methods is used for data collection by interviewing students, parents, and teachers, while the Waterfall model is used for system development. Mobile Application is made with Flutter and Web Application is made using PHP with Laravel Framework. The result of the research is to build an attendance system based on a QR-Code that can be scanned by students' smartphones the QR-Code scan results will be stored in the attendance database and attendance information will be sent in real-time via WhatsApp to students' parents' smartphones.